Lost in Transfer? Exploring the Influence of Culture on the Transfer of Knowledge Categories - ALO, OBINNA (My University, 2022)
Supported by an extensive review of four-domains of literature (knowledge management, organisational learning, culture, and retail), this study examines the influence of national culture on transfer of knowledge categories in top supermarkets in Africa and the United Kingdom (UK). Data from in-depth semi-structured interviews with 40 store managers (SMs) was used to examine how the SMs transfer the five sales performance drivers – selling-related knowledge, the degree-of-adaptiveness, role-clarity, cognitive-aptitude, and work-engagement – to their subordinates. The study finds these UK supermarkets’ knowledge transfer (KT) practices as embedded in Problem-Based Learning (PBL) and project-based learning. SMs from African supermarkets exploit various opportunities to build interpersonal relationships and trust with knowledge-holders, thereby facilitating learning and KT. This study links such behaviours to ‘Ubuntu’ – a well-established African philosophy/ethics. The study finds socialisation, externalisation, and internalisation as common knowledge assets in African supermarkets, in contrast to socialisation and externalisation in their UK counterparts. This study found that, despite these variations in their strategic priorities regarding knowledge assets, these five sales performance drivers are transferred successfully in the supermarkets in both continents that participated in the research. This offers a new insight that challenges the extant theorising that KT praxis varies between diverse cultures.
Keywords: Knowledge Categories; United Kingdom; Supermarkets